Pengaruh Aktivitas Fisik Terhadap Peningkatan Kecerdasan Emosi Siswa - Riyanto, Pulung; Mudian, Deni (Journal Sport Area, 2019)
This study is to determine the effect of physical activity on students' emotional quotient. The research method that used is the psychology of emotional quotient, and experimental methods. The results of data calculations, the significance value indicates the number 0.001 <0.05. It shows that there is a significant increase in the emotional quotient of children that are treated by using physical activity. Physical activity that developed at school influences children's emotional quotient. In developing maximum achievement and learning outcomes in school, emotional quotient that possessed by a student is a critical determinant of student success that must be owned. Emotional quotient is very important in the success of life, in this case the success that is emphasized is in life at school. Physical activity that developed in this study has an impact on increasing of children's emotional quotient.